Effect of heat treatment on the physical properties of bimetallic doped catalyst, Cu-Ni/TiO 2 - Bashiri, R. (American Institute of Physics Inc., 2015)
Post heat treatment is critical for the doped semiconductor oxide in order to improve its photocatalytic performance. Thus work had been carried out to understand the effect of different calcination temperature (400, 450 and 500°C) on the physical properties of nanosized Cu-Ni/TiO 2 Cu-Ni doped TiO 2 nanoparticles prepared using a combined method of sol-gel and hydrothermal. The treated samples were characterized using Raman spectroscopy, Brunauer-Emmett-teller (BET) measurement, high resolution transmission electron microscopy (HRTEM), field-emission scanning electron microscopy (FESEM), and diffuse reflectance UV-Vis spectroscopy (DR-UV-Vis). Raman analysis showed that all samples displayed anatase (101) phase of TiO 2 , which is in good agreement with the TEM results. BET data showed that all prepared Cu-Ni/TiO 2 with different calcination temperature are mesoporous. SEM images displayed spherical particles with typical size of about 15 to 20 nm. UV-Vis spectra illustrated that the absorbance edge of all prepared Cu-Ni/TiO 2 have extended to the visible region with bandgap energies (2-2.1 eV) less than the pure anatase TiO 2 (3.2 eV). Calcination temperature of 450°C is considered to be the optimum as it converts the synthesized Cu-Ni/TiO 2 sample to have smaller average particle size with higher surface area that lead to more absorbance in the visible region and lower bandgap energy. © 2015 AIP Publishing LLC.